Increased CD14+ and decreased CD14− populations of monocytes 48 h after zolendronic acid infusion in breast cancer patients. Issue 3 (March 2017) - Kyrgidis, A.; Yavropoulou, M.; Lagoudaki, R.; Andreadis, C.; Antoniades, K.; Kouvelas, D.
Abstract Summary It has been proposed that bisphosphonates cause osteonecrosis of the jaws through impairment of the monocyte population function and proliferation. Such changes have been confirmed in jaw tissues, ex vivo. In this clinical study, we report for the first time a similar pattern of changes in peripheral blood monocytes. Introduction The aim of this study is to examine the effect of zolendronic acid administration in the peripheral blood white cell population, seeking a plausible pathophysiological link between bisphosphonates and osteonecrosis of the jaw. Methods Twenty-four breast cancer patients, under zolendronic acid treatment for bone metastasis, were included. Peripheral blood samples were obtained prior to and 48 h following zolendronic acid administration. Flow cytometry gated at leukocyte, monocyte, and the granulocyte populations for the CD4/CD8/CD3, CD3/CD16+56/CD45/CD19, CD14/CD123, and CD14/23 stainings were performed. Results We were able to record a number of changes in the white cell populations after 48 h of zolendronic acid administration. Most importantly, in the monocyte populations, we were able to detect statistically significant increased populations of CD14+/CD23+ (p = 0.038), CD14+/CD23− (p = 0.028), CD14+/CD123+ (p = 0.070, trend), and CD14+/CD123− (p = 0.043). In contrast, statistically significant decreased populations of CD14−/CD23+ (p = 0.037) and CD14−/CD123+ (p = 0.003) were detected. Conclusions Our results provide evidence supporting the hypothesis that bisphosphonate administration modifies the monocyte-mediated immune response. An increase of CD14+ peripheral blood monocyte (PBMC) populations along with a decrease of CD14− PBMC populations has been recorded. The latter finding is in accordance with limited—currently existing—evidence and warrants further elucidation.